First, second / Daniil Kharms ; translated from the Russian by Richard Pevear ; pictures by Marc Rosenthal. - Kharms, Daniil, 1905-1942 (Farrar, Straus and Giroux, 1996)
A man out for a walk encounters another man, the shortest man in the world, a long man, a donkey, an elephant, and a little dog.